A study on Gambits in English Conversation - Nguyễn Thị Mỹ Phượng; Thái Duy Bảo, PTS (Hà Nội : Đại học Ngoại ngữ Hà Nội, 1999)
This thesis presents a study on Gambits in English conversation.
Keywords: Anh ngữ; English thesis; Luận văn Anh ngữ; English conversation; Gambits; Conversations; English linguistics -- Usage